Teachers Views On Curriculum Changes In Indonesia - Clara Triliana Harefa (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Indonesia's educational system is currently undergoing a significant transformation with the introduction of the "Kurikulum Merdeka Belajar," or Curriculum Freedom of Learning. This shift aims to provide students with a more comprehensive and learner-centered educational experience. As teachers play a pivotal role in this process, it is crucial to understand their perspectives, concerns, and objectives regarding the ongoing curriculum changes. This article presents the findings of a study that delves into the viewpoints of educators from diverse educational backgrounds and levels through a series of in-depth interviews. The research aims to offer a deeper understanding of the implications of the curriculum freedom of learning and to shed light on how teachers perceive and adapt to these changes. By providing educators with a platform to voice their experiences, this study seeks to contribute to a more comprehensive comprehension of the intricate dynamics surrounding curriculum reform and its impact on the teaching profession.